Rancang Bangun Sistem Buku Tabungan Berbasis Website Di SDIT AlManar Lamongan - Tjatursari Widiartin; Arif Nur Rizaluddin; Catenary Febriyanto (Melek IT : Information Technology Journal, 2021)
SDIT Al Manar is an elementary school that educates its students to save money. In the activity of saving money, sometimes teachers who handle the administration of receiving and disbursing savings funds experience problems, namely frequent discrepancies in numbers and unrecorded transactions. The Web-Based Savings Book application can help make it easier for school administration officers to handle student savings transaction data, so that the implementation of money-saving transactions can be done quickly, precisely, and accurately. This passbook application is built using a system development life cycle approach where there are 5 stages, namely problem identification, requirements analysis, system design, coding, and testing. The analysis technique and system design used is object-oriented and described using the case tool of the unified modeling language. The first stage, identification of problems is carried out at the practical work location with observation and interview data collection methods. The second stage, system analysis is carried out to find functional and non-functional requirements which are described by use case diagrams. The third stage is the system design which will be described with a class diagram. The fourth stage, coding is done using the PHP programming language and the MySQL database engine. The fifth stage is testing the application. An abstranct is a brief summary of a research article, thesis, review, conference proceeding or any-depth analysis of a particular subject or disipline, and is often used to help the reader quickly ascertain the paper purposes. When used, an abstract always appears at the beginning of a manuscript or typescript, acting as the point-of-entry for any given academic paper or patent application. Absatrcting and indexing services for various academic discipline are aimed at compiling a body of literature for that particular subject. Abstract length varies by discipline and publisher requirements. Abstracts are typically sectioned logically as an overview of what appears in the paper.